Prolonged grief and perceived mental and physical health: The mediating role of meaning in life - Sarper, E.; Luís, S.; Rodrigues, D. L. (OMEGA - Journal of Death and Dying)
Past research showed that bereaved individuals with higher levels of prolonged grief symptoms report poorer health. However, research addressing the downstream consequences of prolonged grief to physical health and its potential underlying mechanisms is still limited. This study explored whether meaning in life explained the associations of prolonged grief symptoms with mental and physical health outcomes. In a cross-sectional study (N = 332), participants who experienced the death of a family member, a romantic partner, or a close friend 12 months or longer ago completed an online survey. Results showed that higher levels of prolonged grief symptoms were associated with more depression symptoms, higher perceived loneliness, and lower perceived physical health. These associations were explained by the perception of less meaning in life. Our findings offer insights for researchers and mental health professionals that can contribute to improving health among bereaved adults. Implications and suggestions for future research are discussed.